Practical application effect of bionic design replicating from dry lotus leaves surface based on carboxymethyl chitosan incorporated black carrot powder on fried shrimp. (December 2022) - Lei, Liang; Wan, Kang; Zhang, Long; Cong, Mengdi; Wang, Yao; Fu, Yuan; Wang, Liyan; Ren, Lili
Abstract: Air oxidation and microbial contamination are two important causes of food spoilage, which encourages the development of packaging alternatives based on natural polymers (polysaccharides). This study aimed to develop and characterize the bionic films replicating from dry lotus leaves surface based on carboxymethyl chitosan incorporated black carrot powder (BCP), and then used for packaging of fried shrimp during refrigerated storage at 4 ± 1 °C. Physicochemical properties and biological activities of films were evaluated. The bionic surface was showed by scanning electron microscope. Compared with the Control, bionic film without BCP possessed higher thickness, while lower opacity, tensile strength, and water vapor permeability. Bionic films containing BCP possessed higher thickness, opacity, a* (red–green), b* (yellow–blue), tensile strength, oil resistance, and antioxidant activity, while lower moisture content, L* (lightness), elongation, water solubility, and swelling. The incorporation of BCP caused interactions between carboxymethyl chitosan and BCP, and gave rise to the films dark red appearance. Bionic films could extend the shelf life of the fried shrimp up to 12 days by delay the lipid oxidation and inhibit microorganism growth. Inserting bionic design into active food packaging is a bold attempt, and is likely to be a new trend in the future. Graphical Abstract: ga1 Highlights: Bionic films based on carboxymethyl chitosan incorporated black carrot powder (BCP) were developed. Bionic films affected thickness, mechanical, barrier, and optical properties of films. Bionic films containing BCP improved antioxidant activities of films. Bionic films extend the shelf life of the fried shrimp up to 12 days.